Strategy for Improving Quality of Education Based on Akhlakul Karimah - Yoga Sari Prabowo (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2019)
Quality education is education that can produce graduates who have the basic ability to learn, so they can participate and even become pioneers in renewal and change by empowering educational resources optimally through good and conducive learning. Quality education or schools are also called high achieving schools, good schools or successful schools, effective schools and excellent schools. Excellent and quality schools are schools that are able to compete with students outside of school. Also has cultural roots and moral values ​​that are good and strong (akhlakul karimah). Quality education is education that is able to answer the various challenges and problems that will be faced now and in the future. Quality or quality of education is the ability of educational institutions and systems to empower educational resources to improve quality in accordance with the expectations or goals of education through an effective educational process. One of the Islamic educational institutions, namely madrasa as an institution that is able to realize quality education and be able to instill religious values ​​(akhlakul karimah) so that it can realize quality education based on morality based on morals.